Commonwealth infrastructure funding for Australian universities: 2004 to 2011 - Koshy, Paul; Phillimore, John (National Tertiary Education Union, 2013)
This paper provides an overview of recent trends in the provision of general infrastructure funding by the Commonwealth for Australian universities (Table A providers) over the period 2004 to 2011. It specifically examines general infrastructure development and excludes funding for research infrastructure through the Australian Research Council or the research funding programme of the Education Investment Fund.